Evaluación de la actividad insecticida de aceites esenciales de menta (Mentha pulegium) Y eucalipto (Eucalyptus melliodora) para el control del gorgojo de maíz (Sitophilus zeamais). - Morales Velasco, María José (2019)
The use of essential oils extracted from aromatic plants has proven efficient in controlling S. zeamais; corn weevil is one of the main pests that attacks stored corn grains in the world. The losses caused by this insect range between 15% and 25%. The main form of controling the maize weevil is through the use of insecticides and gases such as phosphine that are highly toxic, which harm the health of the farmer and agroecosystems. Less harmful alternatives to control corn weevil are necessary especially for small farmers who grow corn as a livelihood. In addition, its use does not affect the environment nor it affects men. The purpose of this research was to evaluate the insecticidal activity of essential oils of peppermint (M. pulegium) and eucalyptus (E. melliodora) for the control of the S. zeamais. For this purpose, the research was developed in the Laboratorio de uso básico, belonging to the Universidad Técnica Estatal de Quevedo using a population of S. zeamais that was collected in the El Empalme canton and kept under controlled conditions. The experiments performed were distributed in a completely randomized design (DCA) in which four concentrations were evaluated with five repetitions for each essential oil (mint and eucalyptus) in insects exposed to filter paper and corn kernels treated with the oils before mentioned. The concentrations of the essential oils of peppermint (M. pulegium) and eucalyptus (E. melliodora) that were used in the tests with filter paper for both repellency and mortality were: 0,078 µl/cm2; 0,16 µl/cm2; 0,31 µl/cm2; 0,63 µl/cm2, while, for trials with corn grains for both repellency and mortality were: 0.075 µl/g; 0,15 µl/g; 0,3 µl/g; 0,6 µl/g. The results obtained did not show differences between the concentrations used in the mortality tests of S. zeamais when using peppermint and eucalyptus oils. However, repellency effects were observed especially when using eucalyptus oil; suggesting that the use of essential oils could be considered as an alternative for the management of the S. zeamais. Keywords: repellency, mortality, mean lethal concentration, mean lethal time.